Human Rights Mechanisms in Latin America from the Perspective of Intersection of Regional and Universal Human Rights Concepts - N. A. Sheremet (Концепт: философия, религия, культура, 2022)
The article analyzes the intersection of universal and regional human rights concepts in Latin America. The regional approach to human rights protection has been proposed by anthropologists who argue that cultural relativism is the basis for the development of the concept of human rights protection. The evolution of human rights is examined by scholars through the prism of both cultural relativism and universalism. While proponents of the first approach assert the importance of cultural and civilizational particularities, proponents of universalism promote the idea of universal morality. The novelty of this study lies in the examination of a different academic approach to human rights protection that encompasses features of both of the aforementioned concepts in order to provide a more objective picture of the current state of the system of human rights protection. The interaction of these concepts is demonstrated through the example of the system for the protection of women's rights in Latin America, as well as of the rights of other vulnerable groups such as indigenous peoples. This leads to the conclusion that both the universalist and the regionalist approaches to human rights protection are mutually supportive. Furthermore, universal and local moral systems borrow elements from each other despite the contradictions between them. In general, the interaction between universalization and regionalization of human rights is clearly visible in Latin America. The elaboration of a new approach that incorporates the features of the two old ones is necessary in order to better understand this process, since human rights protection is acquiring new features that fit into the so-called paradigm of relative universalism. An explanatory model to account for this phenomenon is needed for better understanding of the common patterns of the process.